Lithium ion battery and electric appliance thereof
By using ternary positive electrode materials and electrolytes equipped with organophosphate compounds and hindered phenol antioxidants in lithium-ion batteries, the problem of temperature loss and low ion transmission efficiency of the battery during circulation is solved, and higher power output capability and safety are achieved.
Patent Information
- Application Number
- CN202411982377.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-14
AI Technical Summary
Existing lithium-ion batteries are prone to heat up and runaway control during circulation and low ion transmission efficiency, resulting in the impact of capacity, circulation and safety.
Using ternary positive electrode material (LiNixCoyMn1-x-yO2) and an electrolyte equipped with organophosphate compounds and hindered phenol antioxidants, the positive electrode material and electrolyte formulation work together to improve the power output capability and safety of the battery.
Effectively prevent the electrolyte from losing control due to heating, improve the battery's power output capability and safety, and optimize the overall performance of the battery.
Smart Images

Figure BDA0005221836150000091 
Figure BDA0005221836150000092 
Figure BDA0005221836150000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a lithium ion battery and an electrical appliance thereof. Background Art
[0002] Since its commercialization in the 1990s, lithium batteries have been widely used because of their high energy density, high charge and discharge efficiency, low self-discharge, long service life and environmental friendliness. At present, they have been applied to consumer electronics, aerospace, military, power tools and electric vehicles. With the development of technology, people have higher and higher requirements for the endurance of lithium-ion batteries in both the consumer field and the power battery field, and the development of high energy density lithium batteries has become the key. The development of high energy density lithium batteries can start from two aspects. One is to develop new high-gram capacity positive and negative electrode materials; the other is to increase the charge and discharge voltage of lithium batteries. Increasing the charge and discharge voltage of lithium batteries can simultaneously increase the mass energy density and volume energy density of lithium batteries, and can also reduce the cost of lithium batteries, which has become a hot topic of research.
[0003] Ternary cathode materials have higher specific capacity and energy density, can store more charge, and achieve longer driving range. Compared with other cathode materials, such as lithium cobalt oxide and lithium ferrite, ternary cathode materials have higher energy density, which can meet the needs of high energy density applications such as electric vehicles. They are used with electrolytes to improve the working voltage and specific capacity of ternary lithium batteries, while inhibiting the structural phase change of the cathode under high voltage. However, the catalysis of nickel in ternary electrolyte is carried out under high voltage conditions. The catalytic effect of nickel elements will accelerate the decomposition of the electrolyte, causing the electrolyte to oxidize and produce gas, especially LiPF6 in the electrolyte will degrade to generate trifluorophosphorus oxyfluoride and HF, which is more destructive to the battery. At the same time, cracks will appear in the pole piece and the dissolved transition metal ions such as manganese and cobalt will also destroy the SEI film on the negative electrode, causing the capacity, cycle and safety of the battery to be seriously affected in high temperature environments.
[0004] In view of this, it is indeed necessary to provide a technical solution to the above problems. Summary of the invention
[0005] One of the purposes of the present invention is to provide a lithium ion battery to address the deficiencies of the prior art, so as to improve the problems of runaway temperature rise and low ion transmission efficiency of the current lithium ion battery during the cycle process.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A lithium-ion battery, comprising a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte; the positive electrode sheet comprises a positive electrode active material, the chemical formula of the positive electrode active material is LiNi x Co y Mn1-x-y O2, where 0.4 < x < 0.6, 0.1 < y < 0.3, and x + y < 1; the electrolyte includes a lithium salt, a non-aqueous organic solvent, and an additive, the additive includes an organic phosphate compound and a hindered phenol antioxidant; the organic phosphate compound accounts for w1% of the mass of the electrolyte, the hindered phenol antioxidant accounts for w2% of the mass of the electrolyte; the non-aqueous organic solvent accounts for w3% of the mass of the electrolyte; wherein, w1, w2, and w3 satisfy the relationship: 0 < (W1 + W2) / W3 < 0.1.
[0008] Preferably, the organic phosphate compound accounts for w1% of the mass of the electrolyte is 1 - 5, the hindered phenol antioxidant accounts for w2% of the mass of the electrolyte is 1 - 3; the non-aqueous organic solvent accounts for w3% of the mass of the electrolyte is 60 - 80.
[0009] Preferably, the organic phosphate compound includes at least one of diphenyl phosphate, triphenyl phosphate, trimethyl phosphate, tolyldiphenyl phosphate, ethyl hexafluorophosphate, propyl pentafluorophosphate;
[0010] The hindered phenol antioxidant includes at least one of butylated hydroxyanisole, dibutylhydroxytoluene, tert-butylhydroquinone, 2,6-di-tert-butyl-4-methylphenol.
[0011] Preferably, the additive further includes a conductive additive, the conductive additive accounts for w4% of the mass of the electrolyte, wherein, w1, w2, and w4 satisfy the relationship: 0 < (W1 + W2) / W4 < 4.
[0012] Preferably, the conductive additive accounts for w4% of the mass of the electrolyte is 1 - 3.
[0013] Preferably, the conductive additive includes at least one of ethylene sulfate, triethyl borate, 1,3-propane sultone, triphenyl borate, tris(hexafluoroisopropyl) borate;
[0014] Preferably, the negative electrode sheet includes a negative electrode active material, the negative electrode active material includes at least one of soft carbon, hard carbon, carbon nanotubes, expanded graphite, graphene, silicon carbon;
[0015] and / or, the separator is one or a combination of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester, and natural fibers, etc.
[0016] Preferably, the porosity Q of the separator, the pore diameter r of the separator, and the thickness h of the separator satisfy the relationship: Q = 4r / 3h.
[0017] Preferably, the internal resistance of the battery is 10 to 75 mΩ.
[0018] A second object of the present invention is to provide an electrical appliance, comprising the lithium-ion battery according to any one of the above.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: The lithium-ion battery provided by the present invention, by improving the cathode material and providing a matching electrolyte formulation, the components of the electrolyte have a synergistic effect, which can prevent the electrolyte from getting out of control due to temperature rise. At the same time, the use of the cathode material and the electrolyte together also improves the power output ability and safety of the battery, thereby optimizing the overall performance of the battery. Detailed Embodiments
[0020] To make the technical solutions and advantages of the present invention clearer, the present invention and its beneficial effects will be further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto.
[0021] The terms "first" and "second" are only used for descriptive purposes, and cannot be construed as indicating or implying relative importance or implicitly specifying the quantity of the indicated technical features. Thus, features defined with "first" and "second" may explicitly or implicitly include one or more of such features. In the description of the present invention, "a plurality" means two or more, unless otherwise specifically defined.
[0022] In the first aspect of the present invention, a lithium-ion battery is provided, comprising a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte; the positive electrode sheet comprises a positive electrode active material, and the chemical formula of the positive electrode active material is LiNi x Co y Mn 1-x-y O2, wherein, 0.4 < x < 0.6, 0.1 < y < 0.3, and x + y < 1; the electrolyte comprises a lithium salt, a non-aqueous organic solvent and an additive, and the additive comprises an organic phosphate compound and a hindered phenol antioxidant; the organic phosphate compound accounts for w1% of the mass of the electrolyte, and the hindered phenol antioxidant accounts for w2% of the mass of the electrolyte; the non-aqueous organic solvent accounts for w3% of the mass of the electrolyte; wherein, w1, w2 and w3 satisfy the relationship: 0 < (W1 + W2) / W3 < 0.1.
[0023] The present invention adopts a ternary positive electrode material in combination with an electrolyte. The ternary positive electrode material has the advantages of high energy density and stable structure, and compared with other positive electrode materials, it has higher safety performance and adapts to a wider operating temperature range; however, the first charge and discharge efficiency of the ternary positive electrode material is relatively low, resulting in a large capacity loss of the battery and low first efficiency. At the same time, although the ternary positive electrode material has good safety performance, once thermal runaway of the battery occurs, it may release toxic and harmful fumes, posing a threat to human health and environmental safety.
[0024] Therefore, the present invention is provided with an electrolyte solution, which includes an organic phosphate compound and a hindered phenol antioxidant. Adding organic phosphate to the electrolyte solution can increase the concentration of mobile ions in the electrolyte, thereby increasing the conductivity of the electrolyte and the conductive performance of the battery, thereby indirectly improving the primary efficiency of the ternary positive electrode material.
[0025] In addition, the metal electrodes in the battery are susceptible to corrosion by ions and oxidants in the electrolyte. Organic phosphates can inhibit metal corrosion by forming a protective film or coordinating with the metal. This coordination can change the charge distribution on the metal surface, reduce the direct contact between the metal and the electrolyte, reduce the rate of metal corrosion, and extend the service life of the battery. Organic phosphates have high chemical and thermal stability in the electrolyte. It can react with water molecules in the electrolyte to form phosphates and esters, thereby reducing the content of water molecules and reducing the evaporation and decomposition rate of the electrolyte, which helps to improve the cycle life and stability of batteries and energy storage devices; organic phosphate systems mainly prevent combustion through free radical elimination reactions. For example, in the flame, trimethyl phosphate (TMP) evaporates into a gaseous state and decomposes to produce phosphorus-containing free radicals, which then combine with H· to inhibit combustion.
[0026] The use of hindered phenol antioxidants and organic phosphates can further enhance the antioxidant properties of the electrolyte. Hindered phenol antioxidants prevent oxidation reactions between organic solvents and electrode materials in the electrolyte. Organic phosphates have poor compatibility in lithium-based batteries and are incompatible with graphite negative electrodes, making it difficult to form a stable SEI on the surface. This drawback can be improved by adding hindered phenol antioxidants, which help stabilize the SEI film and improve the charge and discharge capacity retention rate of the graphite electrode. In addition, hindered phenol antioxidants have a synergistic effect when used in combination with phosphites in organic phosphates, which can improve the alkali resistance and electrochemical stability of the diaphragm.
[0027] In some embodiments, the phosphate compound accounts for 1-5 w1% of the electrolyte mass, the hindered phenol antioxidant accounts for 1-3 w2% of the electrolyte mass; and the non-aqueous organic solvent accounts for 60-80 w3% of the electrolyte mass.
[0028] In some embodiments, the organic phosphate compound includes at least one of diphenyl phosphate, triphenyl phosphate, tolyl diphenyl phosphate, ethyl hexafluorophosphate, and propyl pentafluorophosphate; preferably diphenyl phosphate and triphenyl phosphate.
[0029] The hindered phenol antioxidant includes at least one of butylated hydroxyanisole, butylated hydroxytoluene, tert-butylhydroquinone, and 2,6-di-tert-butyl-4-methylphenol, preferably butylated hydroxyanisole.
[0030] In some embodiments, the additive further includes a conductive additive, and the conductive additive accounts for w4% of the mass of the electrolyte, wherein w1, w2 and w4 satisfy the relationship: 0<(W1+W2) / W4<4.
[0031] In some embodiments, the conductive additive accounts for 1-3% of the electrolyte mass.
[0032] The electrolyte also includes conductive additives. The presence of conductive additives will affect the distribution of the electrolyte in the battery system. If the content of conductive additives is too low, the conductive channels will be reduced, which is not conducive to large current charging and discharging. If the content of conductive additives is too high, the relative content of active substances will decrease and the battery capacity will decrease. At the same time, conductive additives help to reduce the internal resistance of the battery and reduce polarization to improve the overall performance of the battery.
[0033] In some embodiments, the conductive additive includes at least one of vinyl sulfate, triethyl borate, 1,3-propylene sultone, triphenyl borate, and tris(hexafluoroisopropyl)borate.
[0034] In some embodiments, the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes at least one of soft carbon, hard carbon, carbon nanotubes, expanded graphite, graphene, and silicon carbon;
[0035] And / or, the diaphragm is a combination of one or more of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fiber, preferably a multilayer composite diaphragm of polyethylene and polypropylene.
[0036] The ternary positive electrode material in the present invention cooperates with the multi-layer composite diaphragm to ensure the safety of the battery at high power output and prevent overheating and short circuit.
[0037] In some embodiments, the porosity Q of the membrane, the pore size r of the membrane, and the thickness h of the membrane satisfy the relationship: Q=4r / 3h.
[0038] In some embodiments, the internal resistance of the battery is 10-75 mΩ.
[0039] The internal resistance of the battery has a significant effect on the discharge rate. Lower internal resistance can reduce energy loss and provide higher power output. If the internal resistance is too high, the battery will generate more heat when discharging at high current, which will not only reduce the efficiency of the battery, but may also affect the safety and life of the battery.
[0040] In an embodiment of the present invention, the preparation method of the positive electrode material includes the following steps: mixing the ternary positive electrode precursor and the lithium salt in a molar ratio, placing them in an atmosphere furnace, sintering them in an air atmosphere, cooling them, grinding them, and sieving them to obtain the ternary positive electrode material.
[0041] In some embodiments, the molar ratio is 1:1-1.2; the sintering temperature is 600-900° C., and the sintering time is 5-12 hours.
[0042] A second aspect of the present invention provides an electrical appliance comprising the lithium-ion battery described above.
[0043] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.
[0044] Example 1
[0045] Cathode material: 500g of ternary precursor Ni 0.5 Co 0.4 Mn 0.1 After (OH)2 and LiOH were mixed evenly in a molar ratio of 1:1.04, they were placed in an atmosphere furnace with an oxygen flow rate of 50 L / min and a heating rate of 1 °C / min. After sintering at 610 °C for 5 h, the mixture was cooled, ground and sieved to obtain the ternary cathode material matrix LiNi 0.5 Co 0.4 Mn 0.1 O2.
[0046] The positive electrode formula is: LiNi 0.5 Co 0.4 Mn 0.1 O2: acetylene black: carbon nanotubes: PVDF = 94%: 3%: 1%: 2%.
[0047] Negative electrode material: graphite: acetylene black: carbon nanotube: PVDF = 95%: 2%: 1%: 2%.
[0048] Electrolyte: 1% diphenyl phosphate (DPP), 1% vinyl sulfate (ES), 2% triethyl borate (TEB), 10% ethylene carbonate (EC), 48% dimethyl carbonate (DMC), 20% diethyl carbonate (DEC), 5% lithium bis(fluorosulfonyl)imide (LiFSI), 10% lithium hexafluorophosphate (LiPF6), 2% vinylene carbonate (VC), 1% butylated hydroxyanisole (BHA).
[0049] Diaphragm: Polyethylene and polypropylene multilayer composite diaphragm
[0050] Battery preparation:
[0051] Prepare positive electrode slurry: Mix the nickel ternary material, conductive agent and binder in proportion to prepare positive electrode slurry.
[0052] Preparation of negative electrode slurry: Graphite material coated with soft carbon and hard carbon, a conductive agent and a binder are mixed in proportion to prepare negative electrode slurry.
[0053] Coating and drying: Coat the positive electrode slurry and negative electrode slurry on aluminum foil and copper foil respectively, dry and cut into required size.
[0054] Stacking and winding: The positive electrode sheet, negative electrode sheet and separator are stacked or wound in multiple layers to form a battery core.
[0055] Liquid injection and packaging: Place the battery core into the battery shell, inject the above electrolyte, and seal it.
[0056] Example 2
[0057] This example differs from Example 1 in that ES and TEB are not added; reduced content is added to DEC;
[0058] The rest is the same as in Example 1 and will not be described again here.
[0059] Example 3
[0060] This example differs from Example 1 in that no DPP is added and a reduced content is added to DEC;
[0061] The rest is the same as in Example 1 and will not be described again here.
[0062] Example 4
[0063] This example differs from Example 1 in that no ES is added and a reduced content is added to DEC;
[0064] The rest is the same as in Example 1 and will not be described again here.
[0065] Example 5
[0066] This example differs from Example 1 in that no TEB is added and a reduced content is added to DEC;
[0067] The rest is the same as in Example 1 and will not be described again here.
[0068] Example 6
[0069] This example differs from Example 1 in that no BHA is added and a reduced content is added to DEC;
[0070] The rest is the same as in Example 1 and will not be described again here.
[0071] Comparative Example 1
[0072] Positive electrode material: ordinary NCM97%: 1% conductive carbon black: 2% PVDF.
[0073] Negative electrode material: ordinary graphite 97%: 1% conductive carbon black: 2% PVDF.
[0074] Electrolyte: 15% ethylene carbonate (EC), 55% dimethyl carbonate (DMC), 13% diethyl carbonate (DEC), 15% lithium hexafluorophosphate (LiPF6), 2% vinylene carbonate (VC).
[0075] Diaphragm: pure PE.
[0076] The rest is the same as in Example 1 and will not be described again here.
[0077] Comparative Example 2
[0078] The difference from Example 1 is the amount of electrolyte additive added, see Table 1 for details;
[0079] The rest is the same as in Example 1 and will not be described again here.
[0080] Comparative Example 3
[0081] The difference from Example 1 is the amount of electrolyte additive added, see Table 1 for details;
[0082] The rest is the same as in Example 1 and will not be described again here.
[0083] Comparative Example 4
[0084] The difference from Example 1 is the amount of electrolyte additive added, see Table 1 for details;
[0085] The rest is the same as in Example 1 and will not be described again here.
[0086] The packaged batteries obtained in Examples 1-6 and Comparative Examples 1 to 4 were subjected to formation and performance tests, and the specific parameters and test results of the above Examples and Comparative Examples are summarized in Tables 1 and 2.
[0087] (1) High temperature cycle performance test: At 45°C, the divided battery is charged to 4.45V at 0.7C constant current and constant voltage, with a cut-off current of 0.05C, and then discharged to 3.0V at 0.5C constant current. After 500 cycles of charge and discharge, the capacity retention rate at the 500th week is calculated. The calculation formula is as follows:
[0088] The 500th cycle capacity retention rate (%) = (500th cycle discharge capacity / first cycle discharge capacity) × 100%.
[0089] (2) 60℃ 14d high temperature storage test: The battery was placed at room temperature and charged and discharged once at 0.5C (4.45V-3.0V), and the discharge capacity C0 of the battery before storage was recorded. The battery was then charged to a full charge state of 4.45V using constant current and constant voltage. After the battery was cooled at room temperature for 24h, the battery was again discharged to 3.0V using 0.5C constant current and constant voltage, and then charged to 4.45V using 0.5C constant current and constant voltage. The discharge capacity C1 and charge capacity C2 of the battery after storage were recorded. The capacity remaining rate and recovery rate of the battery after storage at 60℃ for 14 days were calculated using the following formula:
[0090] After 14 days of storage at 60°C, the remaining capacity = C1 / C0*100%;
[0091] After storage at 60°C for 14 days, the capacity recovery rate = C2 / C0*100%.
[0092] Table 1
[0093]
[0094] Table 2
[0095]
[0096]
[0097] In summary, the present invention improves the power output capacity of the battery, ensures the safety of the battery at high power output, and prevents the battery from overheating and short circuiting by optimizing the electrode material and electrolyte formulation.
[0098] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A lithium ion battery, characterized in that: It includes a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte; the positive electrode sheet includes a positive electrode active material, and the chemical formula of the positive electrode active material is LiNi x Co y Mn 1-x-y O2, where 0.4 < x < 0.6, 0.1 < y < 0.3, and x + y < 1; the electrolyte includes a lithium salt, a non-aqueous organic solvent and an additive, the additive includes an organic phosphate compound and a hindered phenol antioxidant; the organic phosphate compound accounts for w1% of the mass of the electrolyte, and the hindered phenol antioxidant accounts for w2% of the mass of the electrolyte; the non-aqueous organic solvent accounts for w3% of the mass of the electrolyte; where w1, w2 and w3 satisfy the relationship: 0 < (W1 + W2) / W3 < 0.
1.
2. The lithium-ion battery according to claim 1, characterized in that The phosphate compound accounts for 1-5% of the electrolyte by weight, the hindered phenol antioxidant accounts for 1-3% of the electrolyte by weight; and the non-aqueous organic solvent accounts for 60-80% of the electrolyte by weight.
3. The lithium-ion battery according to claim 1, characterized in that The organic phosphate compound includes at least one of diphenyl phosphate, triphenyl phosphate, trimethyl phosphate, tolyl diphenyl phosphate, ethyl hexafluorophosphate, and propyl pentafluorophosphate; The hindered phenol antioxidant includes at least one of butylated hydroxyanisole, butylated hydroxytoluene, tert-butylhydroquinone and 2,6-di-tert-butyl-4-methylphenol.
4. The lithium-ion battery according to claim 3, characterized in that: The additives also include a conductive additive, which accounts for w4% of the mass of the electrolyte, wherein w1, w2 and w4 satisfy the relationship: 0<(W1+W2) / W4<4.
5. The lithium-ion battery according to claim 4, characterized in that: The conductive additive accounts for 1 to 3% of the mass of the electrolyte.
6. The lithium-ion battery according to claim 4, characterized in that: The conductive additive includes at least one of vinyl sulfate, triethyl borate, 1,3-propylene sultone, triphenyl borate, and tris(hexafluoroisopropyl)borate.
7. The lithium-ion battery according to claim 1, characterized in that: The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes at least one of soft carbon, hard carbon, carbon nanotubes, expanded graphite, graphene, and silicon carbon; And / or, the separator is a combination of one or more of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fiber.
8. The lithium-ion battery according to claim 7, characterized in that: The porosity Q of the diaphragm, the pore size r of the diaphragm, and the thickness h of the diaphragm satisfy the relationship: Q=4r / 3h.
9. The lithium-ion battery according to claim 1, characterized in that: The internal resistance of the battery is 10-75 mΩ.
10. An electrical appliance, characterized in that: A lithium ion battery comprising any one of claims 1 to 9.
Citation Information
Cited By
Organic flow battery with high energy density and preparation method thereof
CN120184304A